1995
DOI: 10.1079/nrr19950013
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Diet, Nutrition and Dental Health: an Overview and Update for the 90s

Abstract: L. (1978). Variation in caries prevalence related to combinations of dietarv and oral hvAene habits and chewing fluoride tablets in 4-year-old children. Caries. I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 197 publications
2
18
0
5
Order By: Relevance
“…Models were adjusted for age, sex, race, perceived income, physical activity level, life‐space, depression, and comorbidity scale, because these factors have been shown to affect quality of life 33–42 …”
Section: Resultsmentioning
confidence: 99%
“…Models were adjusted for age, sex, race, perceived income, physical activity level, life‐space, depression, and comorbidity scale, because these factors have been shown to affect quality of life 33–42 …”
Section: Resultsmentioning
confidence: 99%
“…As described above, a significantly higher prevalence of root surface caries was observed in elderly participants aged 65–74‐years‐old, as well as ethnic minorities, nontea drinkers, and those whose household income was <10 000 yuan in the past year. A number of studies demonstrated a significant association between sugary food consumption frequency with root surface caries prevalence (13, 14). However, the results of our analysis did not reach similar statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…It has further been suggested that the caries/sugars relationship may appear generally weak where caries prevalence is low and sugar intakes are high or relatively homogeneous in a population [Burt et al, 1988]. The absence of a significant correlation in Western societies may be because they lie on the upper flattened area of the sigmoid curve that describes the caries/sugar relationship [Moynihan, 1995]. Recently, Woodward and Walker [1994] studied mean DMFT scores and per capita sugars consumption in 12-year-olds from 90 countries, and found no evidence of a caries/sugar relationship in the 29 countries that were industrialised.…”
Section: Discussionmentioning
confidence: 99%